2005
DOI: 10.1152/japplphysiol.00965.2004
|View full text |Cite
|
Sign up to set email alerts
|

External compression increases forearm perfusion

Abstract: Application of compression stockings to the lower extremities is a widely used therapeutic intervention to improve venous return, but there is little information about the effects of compression on local arterial perfusion. Therefore, we tested the hypothesis that a positive external pressure increases forearm perfusion. The relation of increasing external pressure induced by standardized compression to the arterial inflow and arterial flow reserve of the forearm was critically evaluated in a group of healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
101
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(111 citation statements)
references
References 23 publications
6
101
0
1
Order By: Relevance
“…To date, it has not been clear whether these cardiovascular alterations are associated with changes in upper body exercise capacity and physical performance, however, there is evidence that compression garments have a positive effect on physical performance in able-bodied athlete populations. [17][18][19] The present study established that wearing compression socks resulted in an improved maintenance of upper body submaximal exercise performance during wheelchair exercise. This finding was accompanied by an increase in arm blood flow suggesting that the improved maintenance of exercise capacity may have been mediated by a more efficient distribution of blood flow to the working muscles during exercise.…”
Section: Discussionsupporting
confidence: 58%
“…To date, it has not been clear whether these cardiovascular alterations are associated with changes in upper body exercise capacity and physical performance, however, there is evidence that compression garments have a positive effect on physical performance in able-bodied athlete populations. [17][18][19] The present study established that wearing compression socks resulted in an improved maintenance of upper body submaximal exercise performance during wheelchair exercise. This finding was accompanied by an increase in arm blood flow suggesting that the improved maintenance of exercise capacity may have been mediated by a more efficient distribution of blood flow to the working muscles during exercise.…”
Section: Discussionsupporting
confidence: 58%
“…Previous work on this topic found that external compression on a limb leads to a decrease (40 to 84 mm Hg compression),41 no change (≈37 mm Hg compression),42 or increase (13 to 23 mm Hg compression)43 in resting limb blood flow. The conflicting results may relate to differences in techniques, protocols, populations, types of garment, and the range and duration of compression levels.…”
Section: Discussionmentioning
confidence: 96%
“…Possible influences of greater body coverage appear unknown despite being of principal importance. Augmented local perfusion has been reported for the forearm and leg (Bochmann et al 2005;Mayrovitz and Larsen 1997), and may account for increases in muscle oxygenation (calf) at rest (Bringard et al 2006a). Data on cardiovascular strain during exercise are typically limited to heart rate (HR), and indicate no significant effect during various forms of running (Ali et al 2007(Ali et al , 2010Bringard et al 2006b;Duffield et al 2008;Duffield and Portus 2007;Goh et al 2010;Higgins et al 2009;Houghton et al 2009;Kemmler et al 2009) and cycling (Scanlan et al 2008).…”
Section: Introductionmentioning
confidence: 98%